Enhancing resource management in building restoration through the use of Artificial Intelligence - Donenko, V.I.; Bobrakov, A.A.; Ivanenko, D.S. (Ways to Improve Construction Efficiency, 2023)
In construction, modern technologies are becoming a key factor in achieving resource conservation and improving efficiency. The application of artificial intelligence not only reduces resource consumption but also creates opportunities for optimizing the design processes and organizing construction production. Monitoring systems for the construction process, along with the implementation of advanced IT technologies in the construction industry, contribute to increased accuracy and speed of work execution. This innovative approach to construction not only promotes resource conservation but also creates essential conditions for the sustainable development of the industry. In the construction industry, where a traditional approach prevails, the implementation of artificial intelligence poses a challenge due to the absence of prior practice. As this technology is cutting-edge, a detailed study and practical testing are necessary to elucidate its potential advantages in the construction process. In the future, with the advancement of the industry, the use of artificial intelligence in construction could become a key factor in improving resource conservation, calendar planning, optimizing processes, and refining project management strategies. The purpose of this article is to develop an understanding of the impact of artificial intelligence on calendar planning and its potential application in post-conflict city rebuilding. In contemporary times, artificial intelligence is becoming an increasingly crucial tool in various fields, including project management, industry, and the economic components of post-crisis situations. Its high potential can contribute to addressing issues related to the reconstruction of cities affected by conflicts. Intelligent algorithms can effectively analyze and optimize calendar plans, considering various factors such as available resources, residents' needs, infrastructure, and more. This will enable the development of precise and efficient recovery strategies, ensuring optimal resource utilization and maximum social impact.